Effect of long-term feeding of graded levels of deoxynivalenol on performance, nutrient utilization, and organ health of grower-finisher pigs (35 to 120 kg). (7th April 2021) - Wellington, Michael O; Bosompem, Michael A; Rodrigues, Lucas A; Columbus, Daniel A
Abstract: The objective of this study was to evaluate the effect of long-term feeding of graded levels of deoxynivalenol (DON) on performance, nutrient utilization, and organ health of grower-finisher pigs. A total of 240 mixed-sex grower-finisher pigs (35.9 ± 1.1 kg initial body weight, BW) were randomly assigned to 1 of 4 dietary treatments (6 pigs/pen; 10 pens/treatment) for 77 d. Diets consisted of a control diet without DON (CONT) and diets containing 1, 3, or 5 ppm DON (DON1, DON3, or DON5). Nitrogen-balance was determined in 1 pig/pen during weeks 6 and 12 of the study. Growth performance measures were taken weekly for average daily feed intake (ADFI), average daily gain (ADG), and gain:feed (GF) until day 77. Blood samples were collected on days 0, 14, 42, 56, and 84 from 1 pig/pen for analysis of indicators of liver and kidney function. On day 7, ADG and ADFI for pigs fed DON3 and DON5 diets were lower ( P < 0.05) compared with DON1- and CONT-fed pigs. Overall, ADG and ADFI (days 0 to 77) were lower in DON3- and DON5-fed pigs compared with CONT and DON1 pigs ( P < 0.05), with no difference in GF ( P > 0.05). Final BW was reduced in DON3- and DON5-fed pigs ( P < 0.05) compared with CONT and DON1, which were not different ( P > 0.05). No significant ( P > 0.05) treatment effects were observed on carcass characteristics. In the grower-phase, protein deposition (PD) was reduced in DON3 and DON5 pigs compared with CONT and DON1 pigs ( P < 0.05). In the finisher phase, PD was not affected by dietary treatment ( P > 0.05). There was no effect of dietary treatment on the majority of selected serum chemistry ( P > 0.05). In summary, pigs exposed to diets containing > 1 ppm DON had reduced growth performance with little or no effect on nitrogen utilization, organ health, or carcass characteristics, suggesting that the negative effects of DON may be largely due to depressed feed intake.